FORMATION OF INFORMATION MODELING COMPETENCE IN THE PROCESS OF PHYSICS EDUCATION (American Journal of Technology and Applied Sciences, 2026)
The rapid development of information and communication technologies has significantly transformed educational practices, particularly in science education. One of the essential competencies required in modern education is information modeling competence, which enables learners to represent, analyze, and interpret physical phenomena through various models. This article examines the formation of information modeling competence in the process of physics education. The study explores theoretical foundations, pedagogical approaches, and digital technologies that support the development of modeling skills among students. Special attention is given to computer simulations, virtual laboratories, mathematical modeling, and problem-based learning as effective tools for enhancing students’ understanding of physical concepts.